Analisis Pemborosan Waktu Tunggu Distribusi Bantuan Bahan Pangan oleh PT Pos Baros Menggunakan Lean Management - Witriani, Dina; Retno Prasinta, Widya (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
Distribution of food aid, what activities in the queueing process cause time wastage, what factors cause time wastage, and how to reduce such time wastage. The purpose of this study is to map the existing system, identify non-value-added activities, and provide solutions based on the Lean management approach. The research findings indicate that the food aid distribution system involves three types of Beneficiary Families (KPM): direct KPM, representative KPM, and SPTJM KPM, which go through three main stages: verification counter, documentation (photography), and rice collection. Through process mapping using the Value Stream Mapping (VSM) method and activity classification based on Lean management principles, several non-value-added activities (NVA) were identified. Risk analysis was conducted using the likelihood and severity approach, while the root causes of the issues were analyzed using the Root cause analysis (RCA) method and the 5W+2H approach. The greatest time wastage occurred at the verification counter, primarily due to incorrect queuing, manual data searches, and discrepancies between barcode data and the recipient list (DANOM). The distribution process took a total of 6,387.28 seconds (approximately 1 hour, 46 minutes, and 27 seconds), indicating the inefficiency of the current system. To address this, ten solutions were formulated using the 5W+2H method.